Measurement of the charge asymmetry in $B^{±}→ φK^{±}$ and search for $B^{±}→ φπ^{±}$ decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
The \CP-violating charge asymmetry in $B^{±}→ φ K^{±}$ decays is measured in a sample of $pp$ collisions at 7 TeV centre-of-mass energy, corresponding to an integrated luminosity of 1.0 fb$^{-1}$ collected by the LHCb experiment. The result is $\mathcal{A}_{CP}(B^{±}→ φ K^{±}) = \rm 0.022± 0.021 ± 0.009$, where the first uncertainty is statistical and the second systematic. In addition, a search for the $B^{±}→ φ π^{±}$ decay mode is performed, using the $B^{±}→ φ K^{±}$ decay rate for normalization. An upper limit on the branching fraction $\mathcal{B}(B^{±}→ φ π^{±})< 1.5× 10^{-7}$ is set at 90% confidence level.